Role of biofilm formation, its triggered immune responses and potential new treatments for bacterial eye infections - Aung, Thet Tun (2017)
Bacterial keratitis is the most important leading cause of corneal opacification and blindness around the world. Mycobacterial keratitis is very hard to eradicate while Pseudomonas keratitis is very common and prone to drug resistance problems. In this study, we investigated the Pseudomonas keratitis as a biofilm mode of infection that induces cyclic-di-GMP signaling and forms phagocyte-tolerant microcolonies on mouse cornea. The increased c-di-GMP content in P. aeruginosa was responsible for decreased levels in cytokine production. C-di-GMP reducing agent (Sodium Nitroprusside) was shown to enhance the efficacy of Colisitin treatment in Pseudomonas keratitis. Mycobacteria readily formed biofilms on mouse cornea comprising of large amounts of extracellular DNA. A strong synergism between Amikacin and Fluoroquinolones against Mycobacterium fortuitum has been observed. DNase addition further enhanced the efficacy of anti-mycobacterial drugs by breaking the mycobacterial biofilm matrix. New treatment strategy (combination of Amikacin, Fluoroquinolones and DNase) showed the best efficacy for converting mycobacterial infections.